Measuring fast stochastic displacements of bio-membranes with dynamic optical displacement spectroscopy - Monzel, Cornelia; Schmidt, Daniel; Kleusch, C.; Kirchenbuechler, D.; Seifert, U.; Smith, Ana-Suncana; Sengupta, Kheya; Merkel, Rudolf (Nature Communications, 2015)
Stochastic displacements or fluctuations of biological membranes are increasingly recognized as an important aspect of many physiological processes, but hitherto their precise quantification in living cells was limited due to a lack of tools to accurately record them. Here we introduce a novel technique-dynamic optical displacement spectroscopy (DODS), to measure stochastic displacements of membranes with unprecedented combined spatio-temporal resolution of 20 nm and 10 mu s. The technique was validated by measuring bending fluctuations of model membranes. DODS was then used to explore the fluctuations in human red blood cells, which showed an ATP-induced enhancement of non-Gaussian behaviour. Plasma membrane fluctuations of human macrophages were quantified to this accuracy for the first time. Stimulation with a cytokine enhanced non-Gaussian contributions to these fluctuations. Simplicity of implementation, and high accuracy make DODS a promising tool for comprehensive understanding of stochastic membrane processes.